Simulation on the Effect of Frequency and Ferromagnetic Tubes Specifications by Far Field Eddy Current Examination. Issue 1 (August 2021) - Du, Haoyang; Cui, Lun; Yang, Zhou; Zhu, Daming
Abstract: Tube leakage frequently occurred in on-service fossil power plants. Traditional NDT testing methods, including RT, UT, MT and PT are not applicable for the examination of large amount tubes. Fat eddy current examination is a new technique for testing ferromagnetic tubes defects, such as inner corrosion, thickness reduction and cracks. Far field eddy current simulation and verification for different specification tubes has been carried out. The result shows that the position of far field eddy current moves backwards with the increase of wall thickness and tube ID. To the defects with same size, examination sensitivity is higher in far field eddy current area. When the defect with same size locates in the inner and outer surface of the tube, the change of magnetic intensify differences is approximately the same, which is in accordance with the experimental result and is satisfied with far field eddy current examination theory. It has been concluded that defects in ferromagnetic tubes could be judged and recognized by far field eddy current examination technique, which shows prospective for the on-line examination and safety evaluation for in-service tubes in fossil power plants.